Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Dividend Payout Ratio (DPR) (Studi Kasus Pada Perusahaan Infrastruktur, Utilitas, dan Transportasi yang terdaftar di Bursa Efek Indonesia tahun 2015-2017). - Septi Ning Tyas; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to examine and analyze the effect of Profitability, Liquidity, and Leverage on Dividend Payout Ratio (DPR) in Infrastructure, Utilities, and Transportation Companies Registered on the Stock Exchange for the 2015-2017 Period. The population that is the object of this research are all Infrastructure, Utilities, and Transportation Companies Registered on the Indonesia Stock Exchange for the 2015-2017 period, namely 60 companies. The sampling technique using purposive sampling method, so that 17 companies were obtained. Data analysis in this study using SPSS version 16. The data testing techniques used in this study include normality test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that partially Profitability (ROA) has no significant positive effect on the Dividend Payout Ratio (DPR). Whereas Liquidity (CR) and Leverage (DER) partially have a significant positive effect on the Dividend Payout Ratio (DPR) Keywords: Profitability, Liquidity, Leverage, and Dividend Payout Ratio (DPR)